Sense of community among Malay customers: evidence from western food outlets in Malaysia using Structural Equation Modelling approach (SEM) / Rozita Naina Mohamed … [et al.] - Naina Mohamed, Rozita; Musa, Rosidah; Borhan, Halimahton; Ismail, Shafinar; Abas, Aemillyawaty; Muda, Mazzini (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Malay customers are becoming western food lovers nowadays. Malay consumers contribute to the nation economy, thus the survival of food industry and its longevity prompted the current investigation. The central issue of this research is to unravel empirically the effects of customer’s experience’s antecedents on customer’s experience and subsequently examined its effect on their sense of community. Greeting customer-experience-that-is-synonymous with a particular brand is becoming increasingly recognized as a vital driver of sense of community. This paper aims to address the gaps by empirically investigating the impact of customer’s experience on sense of community. Self-administered questionnaires were distributed through store-intercept at selected western food restaurants such as Starbuck, Kenny Roger’s and Nando’s. 250 useable data from Malay consumers were analyzed using structural equation modelling (SEM) procedure. Several interesting findings are confirmed: (1) service quality is not significant predictors of customer’s experience; (2) customer’s experience has a positive effect on sense of community. These findings have important implications for consumer behaviour literature and retail industry.